리스크 완화를 위한 Wet Scrubber 세정수 pH의 효율적 관리 - 주동연; Dong-yeon Joo; 서재민; Jae Min Seoe; 김명철; Myung-chul Kim; 백종배; Jong-bae Baek (한국안전학회지, 2020)
Wet Scrubber reacts the incoming pollutant gas with cleaning water (water + absorbent) to absorb pollutants and release the clean air to the atmosphere. Wet scrubbers and packed tower scrubbers using this principle are widely used in businesses that emit acid gases. In particular, in the etching process using hydrochloric acid (HCl), alkaline washing water (NaOH) having a pH of about 8 to 11 is used to absorb a large amount of acid gas. However, These salts are attached to the injection nozzle (nozzle), filling material (packing), and the demister (Demister), causing air pollution, human damage, and inoperability due to clogging and acid gas discharge. Therefore, In this study, an improvement plan was proposed to manage the washing water with pH 3~4 acidic washing water. The test method takes samples from the Wet Scrubber flue measurement laboratory twice a month for 1 year. Hydrogen chloride (HCl) concentration (ppm) was measured, and nozzle clogging and scale conditions were measured, compared, and analyzed through a differential pressure gauge and a pressure gauge. As a result of the check, it was visually confirmed that the scale was reduced to 50% or less in the spray nozzle, filler, and demister. In addition, the emission limit of hydrogen chloride in accordance with the Enforcement Regulation of the Air Quality Conservation Act [Annex 8] met 3 ppm or less. Therefore, even if the washing water is operated in an acidic pH range of 3 to 4, it is expected to reduce air pollution and human damage due to clogging of internal parts, and it is expected to reduce maintenance costs such as regular cleaning or replacement of parts.